Enhanced efficacy and specificity of epithelial ovarian carcinogenesis by embedding a DMBA-coated cloth strip in the ovary of rat - Huang Yiping; Jiang Wei; Wang Yisheng; Zheng Yufang; Cong Qing; Xu Congjian (BMC, 2012)
Abstract Background Ovarian cancer is predominant of epithelial cell origin and often present at an advanced stage with poor prognosis. Most animal models of ovarian carcinoma yield thecal/granulose cell tumors, rather than adenocarcinomas. The best reported induction rate of adenocarcinoma in rats is 10-45% by an ovarian implantation of 7, 12-dimethylbenz[a]anthracene (DMBA) coated silk suture. We provided an improved procedure to construct the model by the ovarian implantation of DMBA-coated cloth strip. Methods A sterile suture (as S group) or a piece of cloth strip (as CS group) was soaked in DMBA before ovarian implantation in Wistar rats. Tumor size, incidence rate and pathological type were analyzed. Results Ovarian tumors in rats of CS group were first noted at 16 wk post implantation and reached a cumulative incidence of 75% (96/128) at 32 wk, while the tumor incidence rate in S group at 32 wk was only 46.25% (37/80). The tumor size in CS group (3.63 ± 0.89 cm) was larger than that of S group (2.44 ± 1.89 cm) (P < 0.05). In CS group, there were only two types of tumor formed: adenocarcinoma (90/96) and sarcoma (6/96). While in S group, there were different types, including adenocarcinoma (21/37), squamous carcinoma (3/37), granulosa cell tumor (3/37), sarcoma (4/37), undifferentiated carcinoma with no adeno character (2/37), benign ovarian tumor (2/37), and malignant teratoma (1/37). Conclusion The model in our study yields much higher incidence and specificity of epithelial derived tumors and showed histological similarities to human ovarian cancers, which would be more suitable for therapeutic research.